The mediating effect of working engagement on transparency and commitment of Human Resource Management practices and job performance - Mozael, Bassam Mohsin (Tanjong Malim, 2023)
The mediating effect of working engagement on transparency and commitment of Human Resource Management practices and job performance by Mozael, Bassam Mohsin